Secondary structure of RNA - Uršič, Urša (Matrika, 2020)
Ribonucleic acids (RNAs) are complex biopolymers consisting of mainly four building blocks - nucleotides (adenine (A), cytosine (C), guanine (G) and uracil (U)). Nucleotides are prone to forming hydrogen bonds in pairs A-U and C-G, as well as in some other variations, depending on the RNA nucleotide sequence. Base pairing is the key phenomenon leading to RNA folding into a secondary structure, which gives rise to many different RNA functions. Ongoing research is investigating ways to predict secondary structure, which may improve both current understanding of biological systems as well as design of new bionanotechnological tools.
Keywords: biopolimeri; biopolymers; nucleotides; nukleotidi; ribonucleic acids; ribonukleinske kisline; RNA nucleotide sequence; veriga RNA